FORMATION OF LIFE SUCCESSFULNESS OF SENIOR PUPILS AS A SCIENTIFIC PROBLEM - Kyrychenko, Valentyna; Necherda, Valeriia (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The relevance of the proposed research is determined by the need of developing the theory and practice of education for pupils of general secondary education institutions, in particular their innovative component in response to new social challenges. The purpose of the article is to outline the problematic field of forming the life success among high school pupils in the post-war reality. The tasks of the researchers were to generalise phenomena of success and life success, as well as to highlight the essence and main ideas of the study, its conceptual provisions and theoretical and methodological foundations, and to determine the organisational and pedagogical conditions and target guidelines for the formation of life success of pupils in general secondary education. The theoretical methods chosen are the systematic and structural analysis of psychological and pedagogical sources on the problem and theoretical generalization. As well as the historical and comparative method of studying foreign and domestic experience in shaping the life success of students and analysis of the documentation of general secondary education institutions to determine the content of activities that shape the life success of senior students. The empirical method was an event analysis of the educational practice of general secondary education institutions aimed to develop the student's personalities. The analysis of the content of modern scientific sources devoted to understanding the problem of forming a student’s life success has led to the following conclusions: life success can be considered both as an internal state of a personality, achieved through regular concentration on one's main desires and active actions to implement them, and as a dynamic socio-psychological characteristic of a personality, which implies the presence of socially recognised achievements, a focus on success, and personal satisfaction with the process and results of one's own life. The authors clarify the concept of “life successfulness” as a dynamic phenomenon that is continuously evolving and becoming more complex, as it is a combination of acquired skills and actual experience of a person. According to the researchers, this is a holistic formation, a complex systemic property of a personality that characterises his or her ability to preserve and optimally reproduce, develop oneself, strategies one's life, act productively in various life situations, experience satisfaction from the results of one's own activities, and perform various gender roles based on life-creating knowledge, skills, and prosocial activities. The article also highlights the sensitivity of the high school age for the formation of life success, identifies the organisational and pedagogical conditions and targets for the formation of life success of high school students in the post-war reality. These guidelines are the cultivation of the necessary personal qualities and the development of key life skills of students important for their social adaptation, establishing harmonious interaction with the immediate social environment and successful life.